Exercise induces structural brain changes and elevates irisin levels and enhances functional performance in multiple sclerosis a pilot randomized study - Bilek, Furkan; Deniz, Gulnihal; Elidar, Gozde; Ercan, Zubeyde; Demir, Caner Feyzi (Nature Portfolio, 2026)
Exercise may promote neuroprotection in multiple sclerosis (MS), but the relationships between exercise-induced brain changes, myokine release, and functional improvements are not fully understood. This pilot randomized controlled trial examined the effects of a 12-week progressive resistance training (PRT) program on brain structure, serum irisin levels, and functional performance, measured with the MS functional composite (MSFC), (PRT: *N*=11; control: *N*=10). The PRT group demonstrated increased serum irisin and enhanced motor and cognitive function, including faster walking speed, improved manual dexterity, and better processing speed. Neuroimaging revealed volumetric increases in gray matter, cerebellum, hippocampus, temporal lobe, and caudate nucleus following PRT. Compared to controls, the exercise group showed greater improvements in irisin levels, mobility, and regional brain volumes, particularly in gray matter, cerebellum, and temporal and hippocampal regions. Correlations were observed between cerebellar and frontal lobe volume changes and cognitive gains, while occipital lobe expansion was linked to fine motor improvements. However, no direct association was found between irisin elevation and brain structural changes. These results suggest that PRT induces concurrent neuroplastic adaptations and functional benefits in MS, though the role of irisin may involve mechanisms beyond volumetric effects. Resistance training represents a viable non-pharmacological strategy to support brain health and functional outcomes in MS.
Keywords: Multiple sclerosis; Exercise; Irisin; Brain volume; Neuroplasticity; Cognitive function